Commentary on "Positive Behavioural Support as an alternative to medication". Issue 1 (28th December 2018) - Robinson, Dave
Abstract : Purpose: The purpose of this paper is to provide a commentary on the article by Lee and colleagues, entitled "Positive Behavioural Support as an alternative to medication", from the perspective of Dimensions, a national provider of social care support to people with learning disabilities and/or autism. As a supporter of the NHS England STOMP campaign, Dimensions recognises that people with learning disabilities and/or autism who have displayed "challenging behaviours" are at risk of being wrongly or over prescribed psychotropic medications intended to control that behaviour, and encourages the use of non-medical support strategies as an effective alternative to psychotropic medications. Design/methodology/approach: Dimensions surveyed the approximately 1, 400 people with learning disabilities and/or autism for whom they provide 24-h support. The survey was intended to assess the extent of use of psychotropic medications and the level of adherence to NICE "best practice" guidelines. The survey was the precursor to an awareness raising campaign and development of an operational toolkit intended to inform and empower people supported, families and colleagues to take a more proactive role in the prescription and review of psychotropic medications. Findings: In total, 54 per cent of people surveyed were being prescribed psychotropic medication, of whom 97 per cent had been prescribed one or more medications for at least six months. Around 51 per cent were having six monthly multi-disciplinary reviews and around 31 per cent had not had a multi-disciplinary review within the preceding 12 months. Only 13 per cent of people taking psychotropic medication had a plan in place that was specifically aimed at reducing or stopping the medication. Originality/value: Empowering people to participate in and challenge clinical decision making can have a transformative effect on the lives of a group of people who have experienced a significant negative impact from prolonged use of psychotropic medications.